Method for preparing carbon aerogel microspheres through spray molding
The method of preparing carbon aerogel microspheres through spray forming solves the problems of long preparation cycle, complex process, high cost and difficult to control particle size in the prior art, and achieves low cost, short cycle, simple process and accurate particle size Controlled effect.
Patent Information
- Application Number
- CN202411596559.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing carbon aerogel microsphere preparation methods have problems such as long preparation cycle, complex process, high cost and difficult to accurately control the particle size.
The method of spray forming is used to prepare carbon aerogel microspheres, and the preparation of microspheres is achieved by configuring the precursor solution, spray drying, insulation and aging and high-temperature carbonization. This method can regulate the particle size and specific surface area of the microspheres by controlling the raw material ratio, the fluid shear rate and the carbonization temperature.
It realizes low cost, short preparation cycle, simple process and precise control of microsphere particle size, significantly reduces production costs and improves the performance of microspheres.
Smart Images

Figure CN119461315A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous carbon microsphere preparation, and specifically relates to a method for preparing carbon aerogel microspheres by spray molding. The prepared carbon aerogel microspheres can be promoted and applied in the fields of medicine, catalysis, adsorption, electrochemistry, synthesis, etc. Background Art
[0002] Carbon aerogel is a lightweight porous material with a controllable three-dimensional nano-network structure. It has the characteristics of high porosity, high specific surface area, high conductivity, and stable physical and chemical properties. Carbon aerogel can be divided into three forms according to its morphology: bulk carbon aerogel, carbon aerogel film, and carbon aerogel microspheres. Problems such as long preparation cycle, complex preparation process, and difficulty in large-scale production limit the large-scale commercial application of bulk carbon aerogel and carbon aerogel film. Carbon aerogel microspheres have attracted widespread attention due to their large specific surface area, adjustable pore size distribution, stable chemical properties, low cost, and regular morphology and structure. These advantages give it broad application prospects in the fields of medicine, catalysis, adsorption, electrochemistry, synthesis, etc.
[0003] At present, there are two main methods for preparing carbon aerogel microspheres. One is to crush the block carbon aerogel into microspheres, but the crushing process will increase the production cost of carbon aerogels, and the introduction of impurities in the crushing process cannot be avoided; the other is to directly synthesize microspherical precursors by emulsion method, and then obtain carbon aerogel microspheres by carbonization. However, this method is difficult to control the particle size distribution of microspheres during large-scale production, and more emulsifiers need to be added, which increases the difficulty of subsequent separation and production costs. Therefore, it is necessary to develop a low-cost, short-cycle, and simple process preparation method for carbon aerogel microspheres.
[0004] In order to solve the problem that the particle size distribution of carbon aerogel microspheres is difficult to control, Chinese patent application 201911191327.0 discloses a carbon aerogel microsphere and a preparation method thereof, which is prepared from the following raw materials: phloroglucinol, resorcinol, formaldehyde and a pore-forming agent, wherein the molar ratio of phloroglucinol to resorcinol is 1: (1-50); the molar ratio of the total amount of phloroglucinol and resorcinol to formaldehyde is 1: (0.5-3); the mass ratio of the total amount of phloroglucinol, resorcinol and formaldehyde to the pore-forming agent is 1: (0.01-0.1). The present invention can control the pore size of the carbon aerogel microspheres by controlling the amount of the pore-forming agent. Chinese patent application 202410322920.9 discloses a carbon aerogel microsphere and a preparation method and application, comprising the following steps: adding phenolic resin and curing agent to an organic solvent and stirring and dissolving them to obtain a precursor solution; adding the precursor solution to an oil phase medium and stirring, and obtaining phenolic aerogel microspheres by reaction-induced phase separation to obtain a carbon aerogel microsphere product. The present invention causes the free energy of the system to change and then induces spinodal decomposition, and the particle size and specific surface area of the aerogel microspheres can be effectively controlled by controlling the raw material ratio, fluid shear rate and carbonization temperature. However, compared with the spray molding granulation method, the above two methods still find it difficult to accurately control the particle size of carbon aerogel microspheres. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing carbon aerogel microspheres by spray molding with low production cost, short preparation cycle and the ability to accurately and effectively control the particle size of microspheres, in order to address the problems of long preparation cycle, complex preparation process, high preparation cost and difficulty in accurately controlling the particle size of existing carbon aerogel microspheres.
[0006] To achieve the above-mentioned object of the present invention, a method for preparing carbon aerogel microspheres by spray molding of the present invention is implemented by the following steps:
[0007] (1) Preparation of precursor solution: adding a set amount of carbon source and formaldehyde solution to a container, then adding an appropriate amount of urotropine and sodium hydroxide, heating and continuously stirring to fully dissolve them; after dissolution, raising the temperature and pre-polymerizing for a period of time, adding an appropriate amount of solvent and polyacrylic acid after pre-polymerization and stirring evenly to obtain a precursor solution; the amount of urotropine is 0wt%-20wt% of the total amount of the carbon source and formaldehyde solution, and the amount of sodium hydroxide is 0.5wt%-6wt% of the total amount of the carbon source and formaldehyde solution; the carbon source is one or more of glucose, melamine, phenol, and resorcinol; the amount of polyacrylic acid is 0%-10% of the volume fraction of the solvent; the solid content of the prepared precursor solution is 1%-30%;
[0008] (2) spray drying: the precursor solution prepared in step (1) is spray dried at a feed temperature of 100-180° C. to obtain organic microspheres;
[0009] (3) thermal aging: the organic microspheres obtained in step (2) are thermally aged at 80-180° C. for a period of time to further crosslink the microspheres;
[0010] (4) High-temperature carbonization: The organic microspheres aged in step (3) are subjected to high-temperature carbonization in an inert gas atmosphere and high-temperature activation in a carbon dioxide gas atmosphere using a fluidized bed to obtain monodisperse carbon aerogel microspheres; the high-temperature carbonization temperature is controlled in the range of 750-1050°C, and the high-temperature activation temperature is controlled in the range of 750-1050°C.
[0011] Experimental studies have shown that chitosan can also be used to replace glucose in the method of the present invention.
[0012] Preferably, in step (1), the amount of hexamine is preferably 1wt%-8wt% of the total amount of the carbon source and the formaldehyde solution, and the amount of sodium hydroxide is preferably 1wt%-6wt% of the total amount of the carbon source and the formaldehyde solution.
[0013] Preferably, in step (1), the proportion of glucose in the carbon source is 0%-100%, the proportion of melamine in the carbon source is 0%-100%, the proportion of phenol in the carbon source is 0%-100%, and the proportion of resorcinol in the carbon source is 0%-100%; the molar ratio of the carbon source to formaldehyde is 1:(1-5).
[0014] Preferably, the solvent in step (1) is a mixture of ethanol and water, and the volume ratio of water to ethanol is 1:(0-2).
[0015] Preferably, in step (1), the dissolution temperature is 30-70°C; the insulation prepolymerization temperature is 50-100°C, and the insulation prepolymerization time is 2-24h.
[0016] Preferably, in step (1), the amount of polyacrylic acid used is 3%-10% of the volume of the solvent.
[0017] Preferably, in step (1), the solid content of the prepared precursor solution is 1%-30%.
[0018] Preferably, in step (2), the feed temperature is 110-180°C.
[0019] Preferably, in step (3), the thermal aging time is 6-32h.
[0020] Preferably, in step (4), the carbonization time is 1-8 h and the activation time is 4-24 h.
[0021] Compared with the prior art, the method for preparing carbon aerogel microspheres by spray molding of the present invention has the following advantages:
[0022] (1) The present invention can replace the most common and expensive resorcinol currently used to synthesize carbon aerogels with lower-priced phenol, glucose, chitosan, etc., which can significantly reduce production costs.
[0023] (2) The present invention adopts a spray direct granulation method, which simplifies the preparation process of carbon aerogel microspheres, shortens the preparation cycle, avoids the introduction of impurities during the preparation of carbon aerogel microspheres, and can effectively control the particle size of carbon aerogel microspheres.
[0024] (3) When chitosan and melamine are used as carbon sources, nitrogen can be introduced into carbon aerogel microspheres, which can effectively improve the performance of carbon aerogel microspheres when used in catalysis, electrochemistry and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a microscope photograph of the organic microspheres prepared in Example 1 of the method of the present invention;
[0026] Figure 2 This is a microscope photograph of the organic microspheres prepared in Example 2 of the method of the present invention. DETAILED DESCRIPTION
[0027] To describe the present invention, a method for preparing carbon aerogel microspheres by spray molding of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but this is not intended to limit the present invention.
[0028] In the examples, the amounts of urotropine and sodium hydroxide refer to the percentages of the total amount of the carbon source and the formaldehyde solution; the amount of polyacrylic acid refers to the percentage of the volume of the solvent; and the solid content refers to the solid content in the prepared precursor solution.
[0029] Example 1
[0030] The carbon source used in this embodiment is phenol, and the molar ratio of phenol to formaldehyde is 1:1; the ratio of water to ethanol in the solvent is 5:5; the solid content is 5%; the amount of hexamethylenetetramine is 8wt%; the amount of sodium hydroxide is 1wt%; and the amount of polyacrylic acid is 5%.
[0031] Phenol, formaldehyde, hexamethylenetetramine and sodium hydroxide were added into a beaker in sequence, stirred and mixed evenly at 70°C, and then heated to 90°C and kept warm for 4 hours. After prepolymerization, the solvent and polyacrylic acid were stirred evenly to form a precursor solution.
[0032] The organic microspheres were spray dried and granulated at an inlet temperature of 120°C using a spray dryer. The obtained organic microspheres were then dispersed on aluminum foil and placed in an oven for aging at 140°C for 12 hours. Finally, the aged organic microspheres were carbonized at 800°C for 4 hours on a fluidized bed and then activated at 850°C for 12 hours to obtain monodispersed carbon aerogel microspheres.
[0033] Example 2
[0034] The carbon sources used in the embodiment are glucose and melamine, the molar ratio of glucose to melamine is 7:1; the molar ratio of the carbon source to formaldehyde is 1:1.5; the ratio of water to ethanol in the solvent is 1:2; the solid content is 15%; the amount of hexamethylenetetramine is 0wt%; the amount of sodium hydroxide is 6wt%, and the amount of polyacrylic acid is 10%.
[0035] Glucose, melamine, formaldehyde and sodium hydroxide were added into a beaker in sequence, stirred and mixed evenly at 60°C, and then heated to 70°C and kept warm for 12 hours. After pre-polymerization, the solvent and polyacrylic acid were stirred evenly to form a precursor solution.
[0036] The organic microspheres were spray dried and granulated at an inlet temperature of 110°C. The organic microspheres were dispersed on aluminum foil and placed in an oven for aging at 180°C for 6 hours. Finally, the aged organic microspheres were carbonized on a fluidized bed at 750°C for 6 hours and then activated at 800°C for 18 hours to obtain monodispersed carbon aerogel microspheres.
[0037] Example 3
[0038] The carbon source used in the embodiment is glucose; the molar ratio of the carbon source to formaldehyde is 1:2; the ratio of water to ethanol in the solvent is 1:0; the solid content is 30%; the amount of hexamethylenetetramine is 20wt%; the amount of sodium hydroxide is 2wt%, and the amount of polyacrylic acid is 0%.
[0039] Glucose, formaldehyde and sodium hydroxide were added into a beaker in sequence, stirred and mixed evenly at 40°C, and then heated to 60°C and kept warm for 24 hours. After pre-polymerization, the solvent and polyacrylic acid were stirred evenly to form a precursor solution.
[0040] The organic microspheres were spray dried and granulated at an inlet temperature of 180°C. The organic microspheres were dispersed on aluminum foil and placed in an oven for aging at 80°C for 32 hours. Finally, the aged organic microspheres were carbonized at 1050°C for 1 hour on a fluidized bed and then activated at 1050°C for 4 hours to obtain monodispersed carbon aerogel microspheres.
[0041] Example 4
[0042] The carbon source used in the embodiment is melamine; the molar ratio of the carbon source to formaldehyde is 1:5; the ratio of water to ethanol in the solvent is 1:2; the solid content is 1%; the amount of hexamethylenetetramine is 1wt%; the amount of sodium hydroxide is 1wt%; and the amount of polyacrylic acid is 3%.
[0043] Melamine, formaldehyde and sodium hydroxide were added into a beaker in sequence, stirred and mixed evenly at 60°C, and then heated to 100°C and kept warm for 2 hours. After pre-polymerization, the solvent and polyacrylic acid were stirred evenly to form a precursor solution.
[0044] The organic microspheres were spray dried and granulated at an inlet temperature of 120°C using a spray dryer. The obtained organic microspheres were then dispersed on aluminum foil and placed in an oven for aging at 100°C for 24 hours. Finally, the aged organic microspheres were carbonized at 750°C for 8 hours on a fluidized bed and then activated at 750°C for 24 hours to obtain monodispersed carbon aerogel microspheres.
[0045] Example 5
[0046] The carbon sources used in the embodiment are phenol and melamine; the molar ratio of the carbon source to formaldehyde is 1:2; the ratio of water to ethanol in the solvent is 2:1; the solid content is 4%; the amount of hexamethylenetetramine is 8wt%; the amount of sodium hydroxide is 2wt%, and the amount of polyacrylic acid is 3%.
[0047] Melamine, formaldehyde and sodium hydroxide were added into a beaker in sequence, stirred and mixed evenly at 60°C, and then heated to 100°C and kept warm for 2 hours. After pre-polymerization, the solvent and polyacrylic acid were stirred evenly to form a precursor solution.
[0048] The organic microspheres were spray dried and granulated at an inlet temperature of 120°C using a spray dryer. The obtained organic microspheres were then dispersed on aluminum foil and placed in an oven for aging at 120°C for 12 hours. Finally, the aged organic microspheres were carbonized at 850°C for 6 hours on a fluidized bed and then activated at 850°C for 18 hours to obtain monodispersed carbon aerogel microspheres.
[0049] Example 6
[0050] The carbon source used in the embodiment is resorcinol; the molar ratio of the carbon source to formaldehyde is 1:2.5; the ratio of water to ethanol in the solvent is 8:1; the solid content is 4%; the amount of hexamethylenetetramine is 0wt%; the amount of sodium hydroxide is 1wt%, and the amount of polyacrylic acid is 3%.
[0051] Add resorcinol, formaldehyde and sodium hydroxide into a beaker in sequence, stir and mix evenly at 30°C, then heat to 50°C and keep warm for 24 hours. After pre-polymerization, stir the solvent and polyacrylic acid evenly to form a precursor solution.
[0052] The organic microspheres were spray dried and granulated at an inlet temperature of 110°C. The organic microspheres were dispersed on aluminum foil and placed in an oven for aging at 130°C for 6 hours. Finally, the aged organic microspheres were carbonized at 950°C for 4 hours on a fluidized bed and then activated at 950°C for 10 hours to obtain monodispersed carbon aerogel microspheres.
[0053] Example 7
[0054] The carbon sources used in the embodiment are phenol and resorcinol, and the ratio of phenol to resorcinol is 9:1; the molar ratio of the carbon source to formaldehyde is 1:1.7; the ratio of water to ethanol in the solvent is 4:1; the solid content is 7%; the amount of hexamethylenetetramine is 3wt%; the amount of sodium hydroxide is 1wt%, and the amount of polyacrylic acid is 4%.
[0055] Add phenol, resorcinol, formaldehyde and sodium hydroxide into a beaker in sequence, stir and mix evenly at 40°C, then heat to 60°C and keep warm for 10 hours. After pre-polymerization, stir the solvent and polyacrylic acid evenly to prepare a precursor solution.
[0056] The organic microspheres were spray dried and granulated at an inlet temperature of 120°C using a spray dryer. The obtained organic microspheres were then dispersed on aluminum foil and placed in an oven for aging at 120°C for 8 hours. Finally, the aged organic microspheres were carbonized at 930°C for 4 hours on a fluidized bed and then activated at 930°C for 11 hours to obtain monodispersed carbon aerogel microspheres.
[0057] After testing, the tap density and specific surface area of the precursors prepared in Examples 1-7 after drying and carbonization are shown in Table 1.
[0058] Table 1 Specific surface and pore volume of carbon aerogel microspheres prepared in each example
[0059]
[0060] The organic microspheres prepared in Example 1 and Example 2 were observed using an optical microscope, and the optical microscope photos thereof are shown as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the organic microspheres prepared in this patent have good sphericity and dispersibility. The particle size of the organic microspheres prepared in Example 1 is mainly distributed in the range of 1-5 μm. Figure 2 It can be seen that when hexamethylenetetramine is not added in Example 2, the particle size of the organic microspheres is significantly reduced, and the particle size is less than 1 μm.
[0061] The above description is only a preferred embodiment of the invention and is not intended to limit the invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the invention should be included in the protection scope of the invention.
Claims
1. A method for preparing carbon aerogel microspheres by spray molding, comprising the following steps: (1) Preparation of precursor solution: adding a set amount of carbon source and formaldehyde solution to a container, then adding an appropriate amount of urotropine and sodium hydroxide, heating and continuously stirring to fully dissolve them; raising the temperature after dissolution and prepolymerizing for a period of time, adding an appropriate amount of solvent and polyacrylic acid after prepolymerization and stirring to obtain a precursor solution; the amount of urotropine is 0wt%-20wt% of the total amount of the carbon source and formaldehyde solution, and the amount of sodium hydroxide is 0.5wt%-6wt% of the total amount of the carbon source and formaldehyde solution; the carbon source is one or more of glucose, chitosan, melamine, phenol, and resorcinol; the amount of polyacrylic acid is 0%-10% of the volume fraction of the solvent; the solid content of the prepared precursor solution is 1%-30%; (2) spray drying: the precursor solution prepared in step (1) is spray dried at a feed temperature of 100-180° C. to obtain organic microspheres; (3) thermal aging: the organic microspheres obtained in step (2) are thermally aged at 80-180° C. for a period of time to further crosslink the microspheres; (4) High-temperature carbonization: The organic microspheres aged in step (3) are subjected to high-temperature carbonization in an inert gas atmosphere and high-temperature activation in a carbon dioxide gas atmosphere using a fluidized bed to obtain monodisperse carbon aerogel microspheres; the high-temperature carbonization temperature is controlled in the range of 750-1050°C, and the high-temperature activation temperature is controlled in the range of 750-1050°C.
2. The method for preparing carbon aerogel microspheres by a spray spheronization process as claimed in claim 1, characterized in that: In step (1), the amount of hexamine is 1wt%-8wt% of the total amount of the carbon source and the formaldehyde solution, and the amount of sodium hydroxide is 1wt%-6wt% of the total amount of the carbon source and the formaldehyde solution.
3. The method for preparing carbon aerogel microspheres by spray molding according to claim 1, characterized in that: In step (1), the proportion of glucose in the carbon source is 0%-100%, the proportion of melamine in the carbon source is 0%-100%, the proportion of phenol in the carbon source is 0%-100%, and the proportion of resorcinol in the carbon source is 0%-100%; the molar ratio of the carbon source to formaldehyde is 1:(1-5).
4. The method for preparing carbon aerogel microspheres by spray molding according to claim 1, characterized in that: The solvent in step (1) is a mixture of ethanol and water, and the volume ratio of water to ethanol is 1:(0-2).
5. The method for preparing carbon aerogel microspheres by a spray spheronization process according to claim 1, characterized in that: In step (1), the dissolution temperature is 30-70°C; the insulation prepolymerization temperature is 50-100°C, and the insulation prepolymerization time is 2-24h.
6. The method for preparing carbon aerogel microspheres by a spray spheronization process as claimed in claim 1, characterized in that: In step (1), the amount of polyacrylic acid used is 3%-10% of the volume of the solvent.
7. The method for preparing carbon aerogel microspheres by a spray spheronization process as claimed in claim 1, characterized in that: In step (1), the solid content of the prepared precursor solution is 1%-30%.
8. A method for preparing carbon aerogel microspheres by a spray spheronization process as claimed in claim 1, 2, 3, 4, 5, 6 or 7, characterized in that: In step (3), the heat preservation and aging time is 6-32h.
9. The method for preparing carbon aerogel microspheres by a spray spheronization process as claimed in claim 8, characterized in that: In step (4), the carbonization time is 1-8 hours and the activation time is 4-24 hours.
10. The method for preparing carbon aerogel microspheres by a spray spheronization process according to claim 1, characterized in that: In step (1), the amount of urotropine is 1wt%-8wt% of the total amount of the carbon source and the formaldehyde solution, and the amount of sodium hydroxide is 1wt%-6wt% of the total amount of the carbon source and the formaldehyde solution; the proportion of glucose in the carbon source is 0%-100%, the proportion of melamine in the carbon source is 0%-100%, the proportion of phenol in the carbon source is 0%-100%, and the proportion of resorcinol in the carbon source is 0%-100%; the molar ratio of the carbon source to formaldehyde is 1:(1-5); the solvent is a mixture of ethanol and water, and the volume ratio of water to ethanol is 1:(0-2); the dissolution temperature is 30-70°C; the insulation prepolymerization temperature is 50-100°C, and the insulation prepolymerization time is 2-24h; the amount of polyacrylic acid is 0%-10% of the solvent volume fraction; the solid content in the configured precursor solution is 1%-30%; In step (2), the feed temperature is 110-180°C; In step (3), the thermal aging temperature is 80-180° C., and the thermal aging time is 6-32 h; In step (4), the high-temperature carbonization temperature is controlled in the range of 750-1050°C, and the carbonization time is 1-8h; the high-temperature activation temperature is controlled in the range of 750-1050°C, and the activation time is 4-24h.
Citation Information
Patent Citations
Carbon aerogel microsphere and preparation method thereof
CN110745807A
A kind of carbon aerogel microsphere and its preparation method and application
CN117923467B
Cited By
Preparation method of light and high-temperature-resistant carbon aerogel for electromagnetic shielding
CN121158780A